2018
DOI: 10.5539/jsd.v11n1p44
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Land Use and Land Cover Changes in the Murchison Bay Catchment of Lake Victoria Basin in Uganda

Abstract: The Murchison Bay catchment in the northern shoreline of Lake Victoria basin is a high valued ecosystem because of the numerous human-related activities it supports in Uganda. The catchment has undergone tremendous human-induced land use/cover changes, which have not been quantified. This study aimed at quantifying the land use/cover changes as well as the rate at which these changes occurred over the last three decades in the catchment. This was achieved using remote sensing techniques and Geographic Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…All the counties were found to be characterized by agricultural land (includes surface areas dedicated to the cultivation of crops, vegetables and fruits); water bodies (includes areas under rivers, lakes, swamps and wetlands); grasslands & vegetation (includes areas covered by grasses, shrubs and bushes); bare land (includes exposed rocky or soil surfaces lacking any vegetation cover); forests (includes areas under naturally occurring or planted indigenous and exotic trees) and built-up areas (includes areas under residential, commercial, industrial and infrastructural establishments). The results confirmed findings from previous study which had shown similar land use land cover categories on the Ugandan basin of Lake Victoria [41]. The spatial-temporal coverages of these LULC classes are presented in Tables 2-6.…”
Section: Distribution Pattern and Trends Of Lulc Categoriessupporting
confidence: 89%
“…All the counties were found to be characterized by agricultural land (includes surface areas dedicated to the cultivation of crops, vegetables and fruits); water bodies (includes areas under rivers, lakes, swamps and wetlands); grasslands & vegetation (includes areas covered by grasses, shrubs and bushes); bare land (includes exposed rocky or soil surfaces lacking any vegetation cover); forests (includes areas under naturally occurring or planted indigenous and exotic trees) and built-up areas (includes areas under residential, commercial, industrial and infrastructural establishments). The results confirmed findings from previous study which had shown similar land use land cover categories on the Ugandan basin of Lake Victoria [41]. The spatial-temporal coverages of these LULC classes are presented in Tables 2-6.…”
Section: Distribution Pattern and Trends Of Lulc Categoriessupporting
confidence: 89%
“…Since the 1990s, the relationship between urban expansion and landscape modification has gained much attention from the academicians as urbanisation induced spatial transformation has become an issue of anxiety to both developing and developed nations (Kiggundu et al, 2018). Over the past few decades, developing countries encountered urbanisation, infrastructural development and associated land transformations in or around the fertile tract, primarily due to increasing population, industrialisation, absence of apt land-use policies and recent global economic changes (Yin et al, 2011).…”
Section: Regional To Local Dimensions: Brief Literature Review and Thmentioning
confidence: 99%
“…The map from t 1 (1990) (figure 2) was compared with the map produced at time t 2 (2000) (figure 3) while t 2 (2000) was compared to t 3 (2010) (figure 4) and t 3 (2010) was compared to t 4 (2017) (figure 5) and a complete matrix of categorical change was obtained. Other LULC statistics were computed in three different ways or equations below (Modified from Kiggundu et al, 2017):…”
Section: Image Classification and Land Use Land Cover Dynamicsmentioning
confidence: 99%
“…Likewise, comprehension of complex interdependence between LULC changes and the riparian rural livelihood can guide in critical decision making by policymakers, planners, and other stakeholders (Munthali et al, 2019;World Bank, 2015). Withal, research on small wetlands in tropical Africa showing underlying causes of LULC dynamics using remote sensing and GIS on the landscape are very few while the spectral signatures acquired from satellite imagery for regions within the tropics exhibit minimal band dissociation capabilities amongst the various vegetation types (Wondie et al, 2011;Kindu et al, 2013;Kiggundu et al, 2017). Moreover, past studies in Lake Victoria basin have focused in detail on the ecological, biological and hydrological components (Ajwang' et al, 2016;Khisa et al, 2013;Terer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%